The Role of Alpha Generation In The Development Islamic Education Digitalization Era Kolong Village Bojonegoro - Anwar, Saeful; Setiawan, Hendra (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
The Industrial Period 5.0 is predicted to have the potential to benefit from the rapid expansion of the use of digital technology. However, some challenges must be faced with the emergence of changes in demographic and social aspects and demands for the application of environmentally friendly technologies. While Generation Alpha is a child born from the millennial generation. The term was put forward by Mark McCrindle through Business Insider Magazine. Generation Alpha (2011 – 2025) is most familiar with digital technology and is claimed to be the smartest generation of the previous generation. Generation Alpha is the most familiar with the internet of all time. The digital era has brought many changes in various aspects of human life, including in Islamic education. This paper aims to describe the role of the alpha generation in Islamic education in the digital era. The type of method in this research is qualitative and descriptive research with question and answer methods and discussions with children totaling 10 people in Kolong Village and conducted on June 19, 2023, aged 5-11 years. The results of this study indicate that children aged 5 to 11 years of the alpha generation obtained religious activities carried out during the development of digital technology as follows uploading videos of religious broadcasts and memorizing videos on short video platforms such as TikTok and Instagram, participating in online-based religious competitions such as Musabaqah Tilawatil Qur`an (MTQ) and Musabaqah Hifzhul Qur`an (MHQ) competitions which are held via zoom or upload works via google drive, help explain their peers if there are questions in social media groups related to material that has been taught by the chaplain when there are friends who do not understand, participate in online tausyiyah held by an Islamic boarding school and actively ask questions in a question and answer session related to the latest problems of the Islamic religion, and access material related to Islamic religious learning through trusted sources